Barriers to and promoters of screening for falls in elderly community-dwelling patients by general practitioners: a large cross-sectional survey in two areas of France. (July 2016) - Gaboreau, Yoann; Imbert, Patrick; Jacquet, Jean-Pierre; Royer De Vericourt, Guillaume; Couturier, Pascal; Gavazzi, Gaëtan
Highlights: We conduct a cross-sectional study in two areas in the South-east of France. 28.8% of GPs implemented annual screening for falls each year, 9.3% every 2–5 years. Patient selecting is the main barrier to achieve annual screening for falls. Abstract: The objective was to determine the factors affecting French GPs' implementation of annual screening for falls among patients of 75 years old and over. We conduct a cross-sectional study in two areas in the South-east of France (Savoie and Isère). An anonymized survey was sent by e-mail and/or post in May 2008 to all GPs with a large practice. Reminder letters were sent to GPs who hadn't answered between June and July 2008. Potentials barriers were measured by dichotomous scale. On GPs characteristics (socio-demographic, knowledge, attitude and practice), a multiple logistic regression was performed to identify others factors affecting falls screening. 493 questionnaires were analyzed (26.8%). 65.3% of respondents considered annual screening for falls to be useful, though only 28.8% of them implemented it each year and 9.3% every two to five years. Barriers to achieving annual screening included patient selecting (56.3%), forgetting to screen (26.6%), unsuitable working conditions (18.5%), lack of time (13.3%), of knowledge (13.3%), or of financial compensation (11.1%). Perception of the usefulness of annual screening for falls (OR = 5.38 (2.07–14.08); p = 0.001), satisfaction with medical care for falls (OR = 1.34 (1.09–1.65); p = 0.006) and increased consultation time (OR = 2.65 (1.37–5.13); p = 0.004), were found to have a significant impact on the implementation of annual screening for falls. Asking your patient each year if s/he has had any falls, inquiring about gait and balance disturbance is not time consuming. Finally, to improve a health-related quality of life, GPs should consider fall assessment as a fundamental feature of medical care.